Direct Production of Ferromolybdenum from Molybdenite by Combustion Synthesis Reaction in the Presence of Aluminum - Qaisari, Suhrab Nikjo; Haidari, Zabiullah (Journal for Research in Applied Sciences and Biotechnology, 2024)
In this research, a new method for the direct and in-situ production of ferromolybdenum alloy by the combined aluminothermic reduction of molybdenum sulfide (MoS) and iron oxide Fe2O3 has been introduced and its feasibility has been investigated. Also, in order to investigate the effect of the presence or absence of a desulfurizer on the chemical composition and purity of the product, lime (CaO) and magnesia (MgO) have been used as desulfurizers. Preliminary investigations showed that the heat of reduction of molybdenum sulfide by aluminum is very high. Their reaction can be carried out as a self-promoting combustion synthesis reaction (Self-propagating high-temperature synthesis). Also, preliminary results showed that increasing the amount of iron oxide in the composition of raw materials increases the heat produced by the reaction, which results in the melting of FERROMOLYBDENUM as a reaction product. In order to examine the synthesized phases and analyze the obtained results, the images taken by the scanning electron microscope (scanning electrode microscope) and the data obtained from the analysis (Energy-dispersive spectroscopy) were used. Also, X-Ray Diffraction Analysis was used to analyze the formed slag. The results indicate that the reaction carried out in the presence of magnesia as a desulfurizer is a more successful system in absorbing sulfur from the produced alloy.